No Clamp Complete Parachute Technique for Ascending Aorta Anastomosis in Hybrid Aortic Arch Debranching Surgery - Chen, I-Ming; Chen, Po-Lin; Chang, Hsiao-Huang (The Thoracic and Cardiovascular Surgeon, 2018)
The proper proximal landing zone is a key element for success of endografting in thoracic aortic pathology. If coverage of innominate artery is unavoidable for safe proximal landing, arch debranching surgery is necessary to recruit supra-aortic blood flow before endografting. However, calcified or adhesive ascending aorta makes it difficult to clamp ascending aorta for anastomosis in the first step of arch debranching surgery. We present a novel “no clamp complete parachute technique” to complete this challenging anastomosis.
Keywords: arch debranching surgery; ascending aorta anastomosis; parachute technique